Virus-encoded TLR ligands reveal divergent functional responses of mononuclear phagocytes in pathogenic SIV infection - Wonderlich, Elizabeth R. (2013)
The role of mononuclear phagocytes in the pathogenesis or control of HIV infection is unclear. Here, we monitored the dynamics and function of dendritic cells (DC) and monocytes/macrophages in rhesus macaques acutely infected with pathogenic SIVmac251 with and without antiretroviral therapy (ART). SIV infection was associated with monocyte mobilization and recruitment of plasmacytoid DC (pDC) and macrophages to lymph nodes which did not occur with ART treatment. SIVmac251 single-stranded RNA encoded several uridine-rich sequences that were potent TLR7/8 ligands in mononuclear phagocytes of naive animals, stimulating myeloid DC (mDC) and monocytes to produce TNF-α and pDC and macrophages to produce both TNF-α and IFN-α. Following SIV infection pDC and monocytes/macrophages rapidly became hyporesponsive to stimulation with SIV-encoded TLR ligands and influenza virus, a condition that was reversed by ART. The loss of pDC and macrophage function was associated with a profound but transient block in the capacity of lymph node cells to secrete IFN-α upon stimulation. In contrast to pDC and monocytes/macrophages, mDC increased TNF-α production in response to stimulation following acute infection. Moreover, SIV-infected rhesus macaques with stable infection had increased mDC responsiveness to SIV-encoded TLR ligands and influenza virus at set-point, whereas animals that progressed rapidly to AIDS had reduced mDC responsiveness. These findings indicate that SIV encodes immunostimulatory TLR ligands and that pDC, mDC and monocytes/macrophages respond to these ligands differently as a function of SIV infection. The data also suggest that increased responsiveness of mDC to stimulation following SIV infection may be beneficial to the host.